Environmentally conscious mechanical design (John Wiley & Sons, Inc., 2007)
The first volume of the Wiley series, Environmentally Conscious Mechanical Design focuses on the foundations of environmental design - both understanding it and implementing it. Coverage includes the important technical and analytical techniques and best practices of designing industrial, business, and consumer products that are environmentally friendly and meet environmental regulations.